ANALYSIS OF THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, COMMUNICATION AND MOTIVATION ON EMPLOYEE PERFORMANCE - Susanto, Agus (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
This study aims to examine the effect of transformational leadership and communication on employee performance with work motivation as an intervening variable at the Dr Wahidin Sudirohusodo National Higher Education Foundation, Medan. The number of samples in this study were 76 respondents using simple random sampling method. This type of research is quantitative research using path analysis techniques and questionnaire data. Path analysis hypothesis test is done by using multiple linear analysis, classical assumption test and intervention test. Based on the results of research with hypothesis testing, the variables of transformational leadership and communication partially have a positive and significant effect on work motivation. The transformational leadership and communication variables partially show a significant effect on employee performance. Transformational leadership on employee performance with work motivation as an intervening variable has a positive and significant indirect effect and there is an influence of communication on employee performance with work motivation as an intervening variable. The variables of transformational leadership and communication have a simultaneous effect on work motivation. The variables of transformational leadership, communication, and work motivation simultaneously affect employee performance with a coefficient of determination of 87.8% which means that the variables of transformational leadership, communication and work motivation can explain employee performance as much as 87.8% and the remaining 12, 2% is explained by other variables such as discipline, commitment, compensation and others. Transformational leadership and communication variables have a simultaneous effect on work motivation. The variables of transformational leadership, communication, and work motivation simultaneously affect employee performance with a coefficient of determination of 87.8% which means that the variables of transformational leadership, communication and work motivation can explain employee performance as much as 87.8% and the remaining 12.2% is explained by other variables such as discipline, commitment, compensation and others. Transformational leadership and communication variables have a simultaneous effect on work motivation. Transformational leadership variables, communication.